2017
DOI: 10.1111/mve.12276
|View full text |Cite
|
Sign up to set email alerts
|

Peptidase inhibitors in tick physiology

Abstract: Abstract. Peptidase inhibitors regulate a wide range of physiological processes involved in the interaction between hematophagous parasites and their hosts, including tissue remodeling, the immune response and blood coagulation. In tick physiology, peptidase inhibitors have a crucial role in adaptation to improve parasitism mechanisms, facilitating blood feeding by interfering with defense-related host peptidases. Recently, a larger number of studies on this topic led to the description of several new tick inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 177 publications
(206 reference statements)
0
26
0
Order By: Relevance
“…Noticeably, although several inhibitors of cysteine proteinase (cystatins) were identified, these were nearly ten times less expressed than inhibitors of serine proteases. These inhibitors can be related to the inhibition of mammalian proteases involved in blood coagulation and complement cascades 87 , acting as a regulator of blood 88 and modulation of the tick immune proteolytic cascades, that have been ascribed relevant roles in the interaction with the microbiota and with pathogens 89 . However, it is also possible to speculate that part of these inhibitors might be negative regulators of hemoglobin degradation, as the proteolytic activity involves the release of large amounts of heme, a pro-oxidant molecule 90 .…”
Section: Digestive Cellsmentioning
confidence: 99%
“…Noticeably, although several inhibitors of cysteine proteinase (cystatins) were identified, these were nearly ten times less expressed than inhibitors of serine proteases. These inhibitors can be related to the inhibition of mammalian proteases involved in blood coagulation and complement cascades 87 , acting as a regulator of blood 88 and modulation of the tick immune proteolytic cascades, that have been ascribed relevant roles in the interaction with the microbiota and with pathogens 89 . However, it is also possible to speculate that part of these inhibitors might be negative regulators of hemoglobin degradation, as the proteolytic activity involves the release of large amounts of heme, a pro-oxidant molecule 90 .…”
Section: Digestive Cellsmentioning
confidence: 99%
“…Comparatively, it was evident from previous reports that outer membrane proteins are vaccine candidates and that cytoplasmic proteins are drug targets [ 21 , 109 ]. It is well known that exported proteins are the prominent molecules of interaction with cells infected by pathogens; therefore, they are potential candidates for vaccine targets [ 110 , 111 , 112 , 113 , 114 ]. The antigenicity and allergenicity analysis of target proteins revealed that eight among them were antigenic while the remaining four proteins were non-antigenic and all the target proteins were non-allergen ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Serine protease inhibitors form four groups – Kunitz-domain inhibitors, serpins, trypsin inhibitor-like cysteine-rich domain inhibitors (TIL-domain inhibitors), and Kazal-domain inhibitors – while the cysteine protease inhibitors usually belong to the cystatin family. Tick protease inhibitors and their functions are reviewed elsewhere (Schwarz et al, 2012; Blisnick et al, 2017; Porter et al, 2017; Parizi et al, 2018), and the therapeutic potential of serpins and cystatins was outlined in our previous review (Chmelar et al, 2017). Here we discuss the therapeutic potential of the other two groups, Kunitz- and TIL-domain inhibitors.…”
Section: Tick Salivary Protein Families With Therapeutic Potentialmentioning
confidence: 99%